2016
DOI: 10.1097/pra.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Role of Botulinum Toxin in Depression

Abstract: This study suggests that botulinum toxin A can produce significant improvement in depressive symptoms and is a safe adjunctive treatment for patients receiving pharmacotherapy for depression. Future trials are needed to evaluate the antidepressant effect per se of botulinum toxin A and to further elucidate the underlying antidepressant mechanism of botulinum toxin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 21 publications
2
32
0
1
Order By: Relevance
“…In fact, even a direct effect of OnabotA injection in amelioration of depressive symptoms has been suggested that probably occur via the facial feedback mechanism with consideration of OnabotA as a safe adjunctive treatment to pharmacotherapy for major depressive disorder [63]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, even a direct effect of OnabotA injection in amelioration of depressive symptoms has been suggested that probably occur via the facial feedback mechanism with consideration of OnabotA as a safe adjunctive treatment to pharmacotherapy for major depressive disorder [63]. …”
Section: Discussionmentioning
confidence: 99%
“…Chronic use of benzodiazepines and related drugs (BDZR, such as zopiclone and zolpidem) has been linked in several studies with increased risk of impaired cognitive function, dementia and mortality [93][94][95][96]. However, the effect of insomnia treatment on stroke risk has been rarely assessed.…”
Section: Does Treatment Of Insomnia Prevent Stroke?mentioning
confidence: 99%
“…A subject who experiences a serious adverse event after BoNT-A injection of a dose substantially exceeding that commonly used in the clinic provides an unusual opportunity to investigate the pharmacological and toxicological mechanisms of BoNT-A, especially the effect of BoNT-A on brain function. These observations could contribute to a better understanding of the therapeutic effects of BoNT-A on dystonia [1, 19], spasticity [1, 19], depression [20, 21], and pain [22, 23], among others. Moreover, a better understanding of the mechanisms underlying BoNT-A poisoning could also improve the guidelines for BoNT-A administration, as well as the outcomes, and minimize adverse events.…”
Section: Introductionmentioning
confidence: 99%